Notary's Responsibility for Making Inheritance Certificates That Do Not Involve All Heirs - Susilowati, Ita Niya (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
This study aims to analyze: 1) The notary's responsibility for making a certificate of inheritance that does not involve all heirs. 2) Legal protection for the parties for making a certificate of inheritance that does not involve all heirs. The approach method used in this study is the empirical legal approach method. This type of research is analytical descriptive research. The types and sources of data in this study are primary data and secondary data obtained through interviews and literature studies. The analysis in this study is qualitative. The results of the study concluded: 1) The notary's responsibility for making a certificate of inheritance that does not involve all heirs can be subject to civil liability, criminal liability, responsibility in carrying out his/her position towards the notary and responsibility for the code of ethics. The notary's responsibility in making a certificate of inheritance is seen depending on what errors are in the Deed of Inheritance made by the Notary. The responsibility of a notary is not limited to law alone, but can also be in the form of moral and ethical responsibility, so that in making a certificate of inheritance if the notary makes a mistake or takes actions that are detrimental to the parties or one of the interested parties, the notary must be morally and ethically responsible or fully responsible. 2) Legal protection for the parties for making a certificate of inheritance that does not involve all heirs is Repressive protection can be obtained by other heirs through complaints through court lawsuits, either criminal lawsuits or civil lawsuits. Legal protection for heirs in disputes over making a certificate of inheritance that does not involve all heirs, in addition to receiving repressive protection, actually also receives preventive protection. Preventive legal protection for land ownership rights holders is by registering the land.